2013
DOI: 10.4103/2211-4122.127412
|View full text |Cite
|
Sign up to set email alerts
|

An uncommon pericardial cyst in the central mediastinum: Incremental diagnosis with contrast-enhanced three-dimensional transesophageal echocardiography

Abstract: We report a case of a 76-year-old man, with the occasional finding of a mediastinal cyst because of subtle chronic dysphagia associated to sore throat, belching, and dysphonia. The paraesophageal cyst in the central mediastinum was studied with computed tomography (CT) scan and transesophageal three-dimensional (3D) echocardiography with contrast echo. In order to clarify doubts about localization (intra- versus extrapericardial) of the mediastinal cystic lesion the 3D transesophageal echocardiography (TEE) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Pericardial cysts are congenital lesions that occur due to incomplete fusion of the mesenchymal lacunae that form the pericardium during fetal development. 4 , 5 Their estimated prevalence is 1 in 100,000 people, and they are usually found in the right anterior cardiophrenic angle. 4 , 6 They are often incidentally identified on chest radiography and appear as an enlarged contour of the right heart border but may alter other cardiac borders as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pericardial cysts are congenital lesions that occur due to incomplete fusion of the mesenchymal lacunae that form the pericardium during fetal development. 4 , 5 Their estimated prevalence is 1 in 100,000 people, and they are usually found in the right anterior cardiophrenic angle. 4 , 6 They are often incidentally identified on chest radiography and appear as an enlarged contour of the right heart border but may alter other cardiac borders as well.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 Their estimated prevalence is 1 in 100,000 people, and they are usually found in the right anterior cardiophrenic angle. 4 , 6 They are often incidentally identified on chest radiography and appear as an enlarged contour of the right heart border but may alter other cardiac borders as well. 5 , 6 , 7 Sometimes pericardial cysts resolve spontaneously, although, similar to the other paracardiac cysts, they can also enlarge and eventually result in compromise of other mediastinal structures.…”
Section: Discussionmentioning
confidence: 99%
“…All diagnosed cysts showed as thin-walled, monocular, echo-free structures and with no obvious blood flow signals in two-dimensional echocardiographic images. It is reported that three-dimensional echocardiography adds incremental value to two-dimensional echocardiography in the detection of PCLs, not only allowing accurate measurements of cyst size, but also better demonstrating the structure of the cyst [ 15 , 16 ]. As mentioned above, the clinical features of the PCLs are nonspecific except the enteric cyst.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment is indicated in the case of symptomatic, large-sized asymptomatic cysts, uncertain diagnosis and possibility of malignant potential, atypical location such as close to large vessels, high density on CT, or the presence of complications. Such treatment is required in order to prevent life-threatening emergencies such as airway and/or haemodynamic impairment, or patient's concern 23,32,40,41,[112][113][114] . Thus, any anterior mediastinal lesion should be considered potentially malignant and should be surgically excised as soon as possible 115 .…”
Section: Therapeutic Approachmentioning
confidence: 99%